Evolution of the efficiency and agro-environmental impact of a traditional irrigation land in the middle Ebro Valley (2001-2007) - García-Garizábal, I.; Causapé Valenzuela, J.; Abrahão, R. (Spanish Journal of Agricultural Research, 2009)
Alternatives in irrigation management can lead to the creation of irrigation lands that are more efficient and more respectful towards the environment. The objective of this work is to analyze the evolution of the agro-environmental impact in a traditional irrigation land of the middle Ebro Valley (Spain) which has experienced changes in its management. For such, water, salt and nitrate balances were accomplished in a hydrological basin (95 ha) in 2001, 2005, 2006 and 2007. The drought of 2005 caused more intensive water use (86%), increasing in 33% the irrigation efficiency when compared to 2001 (53%), even though a high hydric deficit (24%) was caused. Changes in the flood irrigation system management (from rotation to ondemand), maximum allocations of irrigation water, billing for the volume of irrigation water consumed and the expansion of crops with lower water and fertilization needs made it possible to achieve irrigation efficiencies of approximately 73% (an increase of 20%) and to halve salt (1.3 Mg ha-1 year-1) and nitrate (25 kg NO3--N ha-1 year-1) loads exported in the drainage. The evaluated management changes have been efficient, but nevertheless, crops still suffer certain hydric stress and since 2005 a slight but worrying negative agro-environmental tendency has been observed and should be reversed.